No Pain, All Gain? : Exchange Rate Flexibility and the Expenditure-Switching Effect - Carriere-Swallow, Yan (IMF Working Papers; Working Paper, 2018)
Theoretical models on the relationship between prices and exchange rates predict that the magnitude of expenditure switching affects the optimal choice of exchange rate regime. Focusing on the transmission of terms-of-trade shocks to domestic real variables we document that the magnitude of the expenditure switching effect is positively associated to the degree of exchange rate flexibility. Moreover, results show that flexible exchange rates allow for significant adjustment in relative prices, which in turn lowers the burden of adjustment on demand for domestic goods and, in some cases, facilitates a faster and more durable external adjustment process. These results, which are robust to accounting for possible non-linearities due to balance sheet effects or currency mismatches, shed new light on the shock absorbing properties of flexible exchange rates.